Advanced ceramics: Evaluation of the mechanism of stock removal and ground surface quality - Bianchi, E. C. [UNESP]; Da Silva, E. J. [UNESP]; Da Silva, C. E. [UNESP]; De Aguiar, P. R. [UNESP]; Valarelli, Ivan de D. [UNESP]; Monici, R. D. [UNESP] (FapUNIFESP (SciELO), 2001)
The aim of this work is to evaluate the mechanism of stock removal and the ground surface quality of advanced ceramics machined by a surface grinding process using diamond grinding wheels. The analysis of the grinding performance was done regarding the cutting surface wear behavior of the grinding wheel for ceramic workpieces. The ground surface was evaluated using Scanning Electron Microscopy (SEM). As a result it can be said that the mechanism of material removal in the grinding of ceramic is largely one of brittle fracture. The increase of the hmax can reduce the tangential force required by the process. Although, it results in an increase in the surface damage, reducing the mechanical properties of the ground component.
Keywords: Advanced ceramics; Diamond wheel; Grinding; SEM; Brittle fracture; Diamond cutting tools; Grinding (machining); Scanning electron microscopy; Surface properties; Wear of materials; Ground surface quality; Stock removal; Ceramic materials